Micromotives and macrobehavior - "Schelling, Thomas C" (New York, 1978)
Micromotives and Macrobehavior was originally published over twenty-five years ago, yet the stories it tells feel just as fresh today. And the subject of these stories$1 (Bhow small and seemingly meaningless decisions and actions by individuals often lead to significant unintended consequences for a large group$1 (Bis more important than ever. In one famous example, Thomas C. Schelling shows that a slight-but-not-malicious preference to have neighbors of the same race eventually leads to completely segregated populations.s
Keywords: Social change